2022
DOI: 10.1155/2022/3404691
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Cinnamon Oil Coating Maintains Quality and Extends Shelf Life of Ready-to-Use Pomegranate Arils under Low-Temperature Storage

Abstract: Different formulations of chitosan (1%, 2%, or 3%) with the incorporation of cinnamon oil (0.25% or 0.50%) were prepared for the preservation of pomegranate aril cv. Bhagwa. Six combinations of chitosan-cinnamon oil formulations along with one control (untreated) were applied to the freshly extracted arils using the dipping application method. All treatments were found to be effective in enhancing the shelf life, improving the postharvest characteristics, and reducing microbial populations on pomegranate arils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Xing et al [33] reported that CS-CO-treated jujube fruit samples significantly controlled the weight loss as compared to control groups by reducing the fruit metabolic-activity-induced transpiration rate. Singla et al [34] tested the CS-CO coating on the pomegranate arils, and their finding showed a significant control against the fruit weight loss as compared to the control samples during storage.…”
Section: Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Xing et al [33] reported that CS-CO-treated jujube fruit samples significantly controlled the weight loss as compared to control groups by reducing the fruit metabolic-activity-induced transpiration rate. Singla et al [34] tested the CS-CO coating on the pomegranate arils, and their finding showed a significant control against the fruit weight loss as compared to the control samples during storage.…”
Section: Weight Lossmentioning
confidence: 99%
“…Vasconcelos et al [79] found that CO and its compounds deter bacterial growth by altering lipid profiles, damaging cell membranes, disrupting ATPases, impeding cell division, affecting membrane porins and motility, and hindering biofilm development, alongside their anti-quorum sensing capabilities. Furthermore, Singla et al [34] observed that using a CS-CO blend on pomegranate arils effectively suppresses aerobic micro-organisms. beginning of the storage period, the yeast and mold growth in the samples ranged between 1.85 and 1.97 log10 CFU/mL.…”
Section: Microbial Growthmentioning
confidence: 99%
“…However, its employment is more popular regarding fresh arils. Often chitosan effectiveness is improved by combination with essential oils for both whole fruit and arils [78,94]. On the other hand, geraniol, thymol, and eugenol have recently been approved, indeed no reliable data are available, although preliminary in vitro trials regarding their efficacy is in progress [95].…”
Section: Disease Controlmentioning
confidence: 99%
“…An edible coating is an exterior layer added to fruits and vegetables to cover the stomata for reducing transpiration,respiration and lowering weight loss (Salehi, 2020). Coatings extend the life of fresh fruits and vegetables by acting as a visible barrier to gases and water while boosting structural integrity (Ojagh et al, 2010;Singla et al, 2022).…”
Section: Introductionmentioning
confidence: 99%